In vitro susceptibility of CD4+ and CD8+ T cell subsets to fludarabine - Gamberale, Romina (2003)
Administration of the adenosine analogue fludarabine (FLU) in vivo induces a profound and prolonged T lymphopenia which mainly affects CD4+ cells. To better understand the mechanistic basis underlying this preferential depletion, we analyzed the in vitro susceptibility of T cell subsets to FLU-induced apoptosis. Contrasting with observations in vivo, our results showed that treatment of peripheral blood mononuclear cells with FLU induced a higher level of apoptosis in CD8+ than in CD4+ T lymphocytes. This increased sensitivity of CD8+ T cells to FLU was observed in samples from both, healthy donors and B cell chronic lymphocytic leukemia patients, and resulted in higher CD4:CD8 ratios in FLU-treated than in untreated cultures (P<0.01). Expression of factors involved in FLU transport and metabolism was then evaluated by quantitative real time-PCR in normal T cell subsets. It was found that mRNA levels of human equilibrative nucleoside transporter-1 nucleoside transporter were higher whereas deoxycytidine kinase and IMP/GMP selective 5′-nucleotidase mRNA levels were lower in CD4 + cells. However the dCK/cN-II ratio was 2-fold greater in CD8 + than in CD4+ T lymphocytes, which could account for the higher apoptosis levels observed in the CD8+ subset. These results favor the view that decreased CD4:CD8 ratios in FLU-treated patients should be attributed to differences in cell recovery and/or homing between T cell subsets. © 2003 Elsevier Inc. All rights reserved.